Rainfall hotspots over the southern tropical Andes: Spatial distribution, rainfall intensity, and relations with large‐scale atmospheric circulation. Issue 5 (11th May 2015) - Espinoza, Jhan Carlo; Chavez, Steven; Ronchail, Josyane; Junquas, Clémentine; Takahashi, Ken; Lavado, Waldo
Abstract The Andes/Amazon transition is among the rainiest regions of the world and the interactions between large‐scale circulation and the topography that determine its complex rainfall distribution remain poorly known. This work provides an in‐depth analysis of the spatial distribution, variability, and intensity of rainfall in the southern Andes/Amazon transition, at seasonal and intraseasonal time scales. The analysis is based on comprehensive daily rainfall data sets from meteorological stations in Peru and Bolivia. We compare our results with high‐resolution rainfall TRMM‐PR 2A25 estimations. Hotspot regions are identified at low elevations in the Andean foothills (400–700 masl) and in windward conditions at Quincemil and Chipiriri, where more than 4000 mm rainfall per year are recorded. Orographic effects and exposure to easterly winds produce a strong annual rainfall gradient between the lowlands and the Andes that can reach 190 mm/km. Although TRMM‐PR reproduces the spatial distribution satisfactorily, it underestimates rainfall by 35% in the hotspot regions. In the Peruvian hotspot, exceptional rainfall occurs during the austral dry season (around 1000 mm in June–July–August; JJA), but not in the Bolivian hotspot. The direction of the low‐level winds over the Andean foothills partly explains this difference in the seasonal rainfall cycle. At intraseasonal scales in JJA, we found that, during northerly wind regimes, positive rainfall anomalies predominate over the lowland and the eastern flank of the Andes, whereas less rain falls at higher altitudes. On the other hand, during southerly regimes, rainfall anomalies are negative in the hotspot regions. The influence of cross‐equatorial winds is particularly clear below 2000 masl.